INNOVATIVE METHODS OF SUPPOTING EDUCATIONAL CONTENT FOR MATHEMATICS - Hulivata, I. (Journal of Information Technologies in Education (ITE), 2019)
The article draws attention to the problem of development of learning and teaching resources for Mathematics on the basis of innovative new methods of introducing learning materials by the use of information technologies. It is emphasized the need for special support to teaching and learning process of Mathematics that are difficult to understand and perceive. It is defined framework for the use of educational technologies in the study of the theory of probabilities on the basis of analysis of didactic possibilities and the generalization of pedagogical experience in the application of modern information technologies. It is defined the necessity of the introduction of the new methodological instructions which mostly emphasizes on the practical part of the studying process, this also must simplify it. It is developed computer models by means of MS Excel, GeoGebra, GRAN1 which are used for automation of calculation, virtual experiment, graphical analysis of data, and give possibility of introducing entertainingly and easily complicated mathematical material without the loss of the main content, which gives rise to students’ cognitive activity and the interest to the learning process. It is designed new approach to support theoretical material by the use of Moodle on a lecture, using as the base educative computer game. It is described the methods of using Web 2.0 cloud technologies during collective and individual learning. These methods are based on the use of Internet sources, giving acessibility, credibility, openness, interactivity and other possibilities for students to create and present their own materials in collective and individual work. The developed materials incorporated in the Moodle learning management system is the foundation of methodical system for teaching the theory of probability by using ICT. Such an integrated approach gives rise in effectiveness of learning due to incorporating this innovative methods for supporting educational content, where the center of the process is a student, who on the base of his individual abilities and interests, implements his individual way of studying.